Development of high-strength, low-cost wrought Mg–2.5 mass% Zn alloy through micro-alloying with Ca and La. (15th November 2015) - Du, Y.Z.; Qiao, X.G.; Zheng, M.Y.; Wu, K.; Xu, S.W.
Abstract: A high-strength low-cost Mg–2.5Zn–0.3Ca–0.4La (mass%) alloy was fabricated by hot extrusion following direct-chill casting. Yield strength (YS), ultimate tensile strength (UTS) and elongation to failure of the alloy are 325 MPa, 341 MPa and 15%, respectively. The high strength of the extruded Mg–2.5Zn–0.3Ca–0.4La alloy is mainly due to grain refinement, dense precipitation and high density of dislocations. The extruded alloy exhibits a bimodal microstructure containing fine dynamic recrystallized (DRXed) grains and deformed regions. High density of dislocations is stored in the deformed regions while dense precipitates are homogeneously distributed in both the DRXed grains and the deformed regions. However, precipitates in the DRXed regions show in spherical shape only, while they are in rod-like shape and spherical shape in the deformed regions. Graphical abstract: Highlights: A novel high-strength Mg–2.5Zn–0.3Ca–0.4La (mass%) alloy is developed. Strength improvement is due to grain refinement, dense precipitates and strain in the deformed region. Trace addition of Ca and La promotes dynamic precipitation during extrusion. Microalloying retards recrystallization and deformed regions remain.